ANALYSIS OF MULTIGRADE TEACHING POLICY IMPLEMENTATION AT ELEMENTARY SCHOOL LEVELS IN PROBOLINGGO DISTRICT - Novelia, Diela (Sekolah tinggi ilmu ekonomi pemuda, 2021)
This study describes analysis for implementing multigrade teaching policies at the primary school level in Probolinggo district, East Java Province. This research is motivated by the phenomenon of teacher shortages in remote areas due to difficult geographical conditions in Probolinggo district. So that the multigrade teaching policy is taken as a solution in overcoming the shortage of teachers. This study uses descriptive qualitative research methods. The case study approach is carried out considering that the multigrade teaching policy is only carried out in certain areas that have special conditions. The research is conducted in Probolinggo district, East Java province. The results show that the multigrade teaching method is considered appropriate to solve the problem of teacher shortages in Probolinggo district. However, improvements are still needed in the implementation of policies and management